2009
DOI: 10.1116/1.3137012
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of photoresist surface modifications during plasma-based pattern transfer on choice of feedgas composition: Comparison of C4F8- and CF4-based discharges

Abstract: The authors report a study of the impact of surface chemical factors on etch rates along with surface and line edge roughness introduction for prototypical photoresist (PR) materials and structures during plasma-based pattern transfer employing fluorocarbon (FC) discharges. For selected photoresist materials and model polymers (193nm PR, 248nm, PR, and polymethyladamantyl methacrylate), the influence of bulk polymer properties on plasma durability was clarified by comparing etch rates, surface roughness introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…But, as reference resist is etched faster, it develops higher roughness for a given processing time. This is consistent with other studies 13,14,35,36 that show that polymers with greater plasma induced material loss present increased surface roughness. The reason is that during steady state etching, the existing surface roughness can be amplified by an ion induced transfer mechanism where locally nonuniform removal rates lead to enhanced surface roughness since low and high surface features will not be etched at the same rate.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…But, as reference resist is etched faster, it develops higher roughness for a given processing time. This is consistent with other studies 13,14,35,36 that show that polymers with greater plasma induced material loss present increased surface roughness. The reason is that during steady state etching, the existing surface roughness can be amplified by an ion induced transfer mechanism where locally nonuniform removal rates lead to enhanced surface roughness since low and high surface features will not be etched at the same rate.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous works. 3,5,13,14,36 Hua et al 13 observed that rough surfaces develop within few seconds of exposure of 193 nm PR to FC plasma, and that the transfer of surface roughness produces rough sidewalls that exhibit vertical aligned features. Similar observations were made on 248 nm photoresist.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2 This change in the material platform introduced new challenges during plasma processing such as increased roughness development, reduced etch resistance, and pattern distortion. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Oehrlein et al have recently reviewed progress on this topic. However, improved CD control by reducing roughness development during plasma etching has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%